Peran Humas dalam Meningkatkan Kepercayaan Walisantri : Studi di Ma`had Tahfidz Al-Qur`an (Putri)PP.Al-Amien Prenduan - Khomsiyatul Mukarromah; Dzelifah Dzelifah (Pusat Riset dan Inovasi Nasional, 2025)
Public relations (PR) plays a vital role in building and maintaining the trust of students’ parents toward Islamic boarding schools (pesantren). This trust serves as an essential foundation for the continuity of education and for fostering a harmonious relationship between the Ma’had and the parents. This study aims to analyze the communication strategies implemented by the Public Relations division of Ma’had Tahfidz Al-Qur’an (Putri) at Pondok Pesantren Al-Amien Prenduan Sumenep in strengthening parents’ trust, to understand their responses to these strategies, and to explore stakeholders’ expectations regarding the management of public relations within the institution. This research employs a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and document analysis. The findings indicate that the PR strategies were carried out through systematic stages of planning, implementation, evaluation, and continuous improvement. Generally, parents expressed satisfaction with the transparency of information, the speed of communication services, and their increased participation in educational activities. However, several aspects still need improvement, particularly in maintaining consistency in financial information delivery and modernizing communication systems through technology. Overall, the PR strategies at Ma’had Tahfidz Al-Qur’an (Putri) have been effective in strengthening parents’ trust and enhancing the institution’s positive image. To further improve the role of PR in the future, it is necessary to enhance staff professionalism, innovate in communication technology, and strengthen collaboration with various stakeholders.